2019
DOI: 10.1104/pp.19.00511
|View full text |Cite
|
Sign up to set email alerts
|

WRKY18 and WRKY53 Coordinate with HISTONE ACETYLTRANSFERASE1 to Regulate Rapid Responses to Sugar

Abstract: Sugars provide a source of energy; they also function as signaling molecules that regulate gene expression, affect metabolism, and alter growth in plants. Rapid responses to sugar signaling and metabolism are essential for optimal growth and fitness, but the regulatory mechanisms underlying these are largely unknown. In this study, we found that the rapid induction of sugar responses in Arabidopsis (Arabidopsis thaliana) requires the W-box cis-elements in the promoter region of GLC 6-PHOSPHATE/ PHOSPHATE TRANS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 69 publications
2
55
0
2
Order By: Relevance
“…Another recent report showed that VaWRKY33 is involved in cold tolerance in Amur grape (Vitis amurensis) (Sun et al, 2019). A more recent study reported that AtWRKY18 and AtWRKY53 directly bind to the promoter of sugar response genes and activate their expression in response to glucose treatment in Arabidopsis (Chen et al, 2019). In our study, we showed that PuWRKY31 was expressed at significantly higher levels in BNG fruit than in NG fruit (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Another recent report showed that VaWRKY33 is involved in cold tolerance in Amur grape (Vitis amurensis) (Sun et al, 2019). A more recent study reported that AtWRKY18 and AtWRKY53 directly bind to the promoter of sugar response genes and activate their expression in response to glucose treatment in Arabidopsis (Chen et al, 2019). In our study, we showed that PuWRKY31 was expressed at significantly higher levels in BNG fruit than in NG fruit (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…MdWRKY40 interacts with MdMYB1 physically, thus enhancing the binding of MdMYB1 to its target genes to induce wounding-induced anthocyanin biosynthesis in apple fruit (An et al, 2019b). WRKY transcription factors respond to sugar treatment by activating the expression of sugar-responsive genes in Arabidopsis (Chen et al, 2019). However, to date, involvement of WRKYs in sugar transport has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Both sugar-induction and sugarrepression cis-acting regions were identified in the promoter of ZjSWEET2.2, including three W boxes (TTGACC/T), which are indispensable for mediating sugar signaling (Sakr et al, 2018). The WRKY-type transcription factors specifically Hwang et al, 1998;Lu et al, 1998; TATCCAOSAMY TATCCA Sugar suppress 2 Lu et al, 2002;Sun et al, 2003Baena-Gonzalez et al, 2007 recognize W-Box cis-elements (Eulgem et al, 2000;Jiang et al, 2017a) and are known to be involved in sugar induction of gene expression (Chen et al, 2019). However, we detected more sugar-repression elements than sugar-induction elements in the promoter of ZjSWEET2.2.…”
Section: Sugar Signals Mediate Expression Of Zjsweet22mentioning
confidence: 99%
“…This indicates that WRKY53 is part of a positive feedback loop also on chromatin level. Very recently, WRKY53 and WRKY18 have been identified to regulate the expression of sugar response genes by recruitment of HISTONE ACETYLTRANSFERASE 1 (HAC1) to facilitate the acetylation of histone 3 Lys 27 (H3K27ac) on their promoters [71].…”
Section: Chromatin Remodeling: Suv2 Powerdress/hda9 Hac1 Jmj16mentioning
confidence: 99%